THE AUTOMATIC PLOTTING OF THE ARCS OF CIRCLE IN THE CHAMFERED HEXAGONAL PRISM CASE REPRESENTATION - Liviu PRUNA; Andrei SLONOVSCHI (Journal of Industrial Design and Engineering Graphics, 2024)
The paper presents a set of equations that stands to the basis of a computer program and to the software themselves, that offers to the user the possibility to automatic draw the arcs used to approximate the representation of a chamfer hexagonal prism. Also, the authors present the way to use software that generates the arcs that approximate hyperbolas resulting on a chamfered hexagonal prism.